Mindfulness mediates the relationship between positive parenting and aggression, depression, and suicidal ideation: A longitudinal study in middle school students - Su, Yanhua; Sun, Wenyan; Gan, Yiqun; Zhu, Qian; Liu, Guoyan; Hui, Linhu; Tang, Hui; Liu, Zhijun (Frontiers in Psychology, 2022)
Previous research has indicated that parenting factors affect the risk of maladaptive psychological outcomes (e.g., aggression, depression, or suicidal ideation), and that positive parenting is a prospective risk factor for maladaptive psychological outcomes. However, the mechanisms underlying the relationships between positive parenting, mindfulness, and maladaptive psychological outcomes remain unknown, as do the processes that mediate the effect of positive parenting on maladaptive psychological outcomes in adolescents. The objective of the present study was to investigate the longitudinal relationship between positive parenting, mindfulness, and maladaptive psychological outcomes in middle school students, as well as the mediating effect of mindfulness in the relationships between positive parenting and depression, aggression, and suicidal ideation. In this study, 386 middle school children (aged 12 to 16) were tested three times over a period of 6 months. Positive parenting was assessed at Time 1, mindfulness at Time 2, and depression, aggression, and suicidal ideation at Time 3. Using structural equation modeling, positive parenting was revealed to be longitudinally associated with mindfulness and negatively associated with maladaptive psychological outcomes. More crucially, mindfulness mediated the relationship between positive parenting and maladaptive psychological outcomes. This research provides important insights into how to effectively decrease adolescent maladaptive psychological outcomes and highlights the importance of teaching mindfulness to youths.